Synthesis and Characterization of Super Paramagnetic Magnetite Nanoparticles for Drug Delivery Application - BALAJ, D; SARALA RUBI, C; G. RENGANATHAN, N (International Journal of Engineering and Technology, 2018)
Attractive nanoparticles have been broadly considered on account of their potential applications as complexity operators in attractive reverberation imaging (MRI) of tumors, cell and DNA partition, attractively guided medication conveyance, tumor hyperthermia. Among the attractive oxides, magnetite nanoparticles are most appropriate because of their low danger and great attractive properties which may be used in drug delivery. Magnetite nanoparticles were synthesized using FeCl3 and FeSO4 as precursors and characterized for size and shape using non-contact AFM.Â  The formation of magnetite was confirmed by XRD pattern. The elemental composition of the obtained phase was determined using EDAX. In this work, we are aiming to develop drug loaded biopolymer Magnetite nanoparticles for biomedical application. Our main objective is to synthesize and characterize Magnetite (Fe3O4) nanoparticles.Â Â